2022
DOI: 10.1089/can.2020.0120
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Profiles in Medical Cannabis Users: Effects of Age, Gender, Symptoms, and Duration of Use

Abstract: Introduction: Clinical trials remain the gold standard for evaluating efficacy, but there is increasing interest in using real-world evidence (RWE) to inform health care decision making. The aims of this observational study were to describe patterns of medical cannabis use, associated changes in symptom severity over time, and to evaluate change in cannabis dose over time for pain-related symptoms. Methods: Data were collected by Strainprint TM , an application that is HIPAA, PIPEDA, and PHIPA compliant. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Recent and ongoing amendments to international laws have resulted in greater access to a range of cannabis products through legalisation for recreational and therapeutic purposes ( Ruheel et al, 2021 ). Cannabidiol (CBD) and Δ9-tetrahydrocannabinol (THC) are the two most well-known compounds found in the cannabis plant, with THC responsible for the psychoactive effects associated with cannabis use, while CBD is known for its potential therapeutic properties ( Kalaba and Ware, 2022 ). Products containing CBD and THC are increasingly utilised for their proposed medicinal properties and are commonly used in combination to manage chronic pain and conditions such as epilepsy, insomnia and anxiety ( Busse et al, 2021 ; Whiting et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent and ongoing amendments to international laws have resulted in greater access to a range of cannabis products through legalisation for recreational and therapeutic purposes ( Ruheel et al, 2021 ). Cannabidiol (CBD) and Δ9-tetrahydrocannabinol (THC) are the two most well-known compounds found in the cannabis plant, with THC responsible for the psychoactive effects associated with cannabis use, while CBD is known for its potential therapeutic properties ( Kalaba and Ware, 2022 ). Products containing CBD and THC are increasingly utilised for their proposed medicinal properties and are commonly used in combination to manage chronic pain and conditions such as epilepsy, insomnia and anxiety ( Busse et al, 2021 ; Whiting et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dominant forms of masculinity are often associated with traits such as stubbornness, self-reliance, and victim-blaming that can lead to under-reporting of psychiatric disorders (especially mood and anxiety disorders) and lack of treatment seeking [ 99 ]. Since there are known gender influences on cannabis use patterns [ 100 ] and sex/gender differences in patterns of CBD use specifically [ 42 , 43 , 44 ], future human studies should consider whether specific gendered dimensions may impact willingness to use CBD and treatment adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Further, human studies have identified sex/gender differences in patterns and motivations of cannabis use, including use for therapeutic purposes [ 40 ]. Of relevance to the present review, recent cross-sectional studies have found that women are more likely to use CBD-only or CBD-dominant cannabis products across a range of patient and non-patient samples [ 42 , 43 , 44 ]. Another recent cross-sectional study of patients with chronic non-cancer pain found that women were significantly more likely to experience adverse effects of medical cannabis (specifically, central nervous system, gastrointestinal, musculoskeletal, and psychological AEs), while also consuming significantly higher monthly doses of CBD than men [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are also a significant number of claims in the media that are difficult to validate but influence patients' consumption of cannabinoid products [17,19,25,[35][36][37][38]. Patients often consume cannabinoids regardless of their efficacy [39,40]. Other confounding variables affecting the assessment of cannabinoid properties are the lack of compound standardization and the increasing variability in their strength and composition [17,19,35,36].…”
Section: Introductionmentioning
confidence: 99%